The observational analysis of elite coaches within youth soccer: The importance of performance analysis - Nicholls, S. B.; Worsfold, P. R. (International Journal of Sports Science & Coaching, 2016)
The study investigated the observational capabilities of experienced elite coaches whilst focusing upon soccer specific actions and playing positions within elite youth soccer. Six soccer coaches assessed the performances of 10 youth soccer players (across 8 matches) on their short/long passing, tackling, shooting, heading and dribbling. Analysis was undertaken on an overall, quality and positional grouping basis. Mean observational accuracy was 38.8%, with successful shooting (78.6%) and passing (29.9%) illustrating the range. The limited effective observation of dribbling (37.2%), often considered a separating factor within talent identification, highlights the need for objective measures to aid such processes. Positional grouping analysis elicited ~20% more effective observation for unsuccessful compared with successful actions. The poor level of observational accuracy identified herein has significant implications on talent identification assessments devoid of post-performance analyses. The findings reinforce the importance of performance analysis in the provision of highly accurate and comprehensive augmented feedback within the coaching process. ABSTRACT FROM AUTHOR